Computational Analysis of Laboratory Scale Fire Whirls With A Ring Plan - Lim, Wen Cong (2017)
Fire whirl is a phenomena that occurs with a bunting fire to form an intensely rotating vertically fire flame with hazard consequences. Currently, there are still lack of researches and studies on fire whirls in terms of experimental and simulation on the characteristics of fire tornado to assist fire fighters to control the phenomenon. This paper will discuss on the study of fire whirl phenomenon and factors that affect the flame height, axial velocity and FFT frequency using Computational Fluid Dynamics (CFD) simulation and FORTRAN 95 to calculate the fluid flow equation and numerical analysis. The manipulative variable in this study is the size of the ring pan. The outcome of this study is to evaluate and discuss on the effect on flame height, axial velocity and FFT frequency with varies ring pan size (ratio outer diameter to inner diameter) of 3.3:1.05, 3.3:0.25 and 3.3:0.3.